Infant formula for gastro-oesophageal reflux disease - C.J.W. Owens; I.L. Labuschagne; M.J. Lombard (South African Family Practice)
Thickened infant formula is widely used as a first-line treatment for gastro-oesophageal reflux (GOR) in infants. The use thereof remains controversial, and conflicting evidence exists with regards to its efficiency. The safety of anti-reflux formula has been proven, with only a few adverse effects reported, making it safe for infants with mild symptoms of reflux.